The Earliest Sound Recordings among North American Inuit - Ross, W. Gillies (ARCTIC, 1984)
On 7 November 1903, Captain George Comer of the American whaling schooner Era recorded on a phonograph a few songs of the Aivilingmiut and Qaernermiut in northwestern Hudson Bay (Ross, 1984:73). These appear to have been the earliest sound recordings ever made among the Inuit of Canada and Alaska. The recordings made by Diamond Jenness among the Copper Eskimos (1914-1916) and those made by Christian Leden among the Padlimiut (1914-1916) have hitherto been considered as the earliest, but Comer's first recording preceded these by more than a decade and his pioneering work should be recognized.